2010
DOI: 10.2527/jas.2009-2435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plane of nutrition and selenium supply during gestation on ewe and neonatal offspring performance, body composition, and serum selenium1

Abstract: To investigate the effects of nutritional plane and Se supply during gestation on ewe and offspring performance and body composition, 84 Rambouillet ewe lambs (age = 240 +/- 17 d, BW = 52.1 +/- 6.2 kg) were allocated to a 2 x 3 x 2 factorial arrangement of treatments. Factors included Se [adequate Se (ASe, 11.5 microg/kg of BW) or high Se (HSe, 77.0 microg/kg of BW)] initiated at breeding, nutritional plane [60% (restricted, RES), 100% (control, CON), or 140% (high, HIH) of NRC requirements] initiated at d 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 26 publications
5
70
1
Order By: Relevance
“…Nutritional requirements were based on NRC (2007) recommendations for a 60-kg body weight pregnant ewe lamb during mid-to late-gestation so that adequate ewes were fed to receive adequate nutrients and energy for maintenance, maternal growth, and fetal growth. This mid-to late-gestation maternal undernutrition model has been previously described in our laboratories (Meyer et al, 2010;Lemley et al, 2012). All ewes were fed and/or supplemented with melatonin-enriched pellets at 1400 h (5 h before the start of the dark cycle at 1900 h).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Nutritional requirements were based on NRC (2007) recommendations for a 60-kg body weight pregnant ewe lamb during mid-to late-gestation so that adequate ewes were fed to receive adequate nutrients and energy for maintenance, maternal growth, and fetal growth. This mid-to late-gestation maternal undernutrition model has been previously described in our laboratories (Meyer et al, 2010;Lemley et al, 2012). All ewes were fed and/or supplemented with melatonin-enriched pellets at 1400 h (5 h before the start of the dark cycle at 1900 h).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Lambs were fed artificial colostrum (45% crude protein; 15% crude fat; 0.15% crude fiber; 10% ash; 0.40% minimum, 0.90% maximum Ca; 0.30% minimum, 0.50% maximum NaCl; 1.0% minimum, 1.5% maximum Na; 0.40% P; 0.75 mg/kg Se; 110 000 IU/kg vitamin A; 2200 IU/kg vitamin D; and 440 IU/kg vitamin E (DM basis); Acquire Colostrum Replacement; APC, Inc., Ankeny, IA, USA) within 30 min of birth and at six additional times by 20 h postpartum to achieve 10.64 g IgG/kg BW (19.1 ml colostrum/kg BW for the first two feedings and 25.5 ml colostrum/kg BW in subsequent feedings; Meyer et al 2010. This dosage of IgG was calculated to provide 50 g IgG/4.7 kg BW based on the previous reports using a similar product (Quigley et al 2002).…”
Section: Parturition and Lamb Managementmentioning
confidence: 99%
“…During gestation, diets were fed once daily at 0800 h in a complete pelleted ration (0.48-cm diameter), and three pellet formulations (ASe pellet, HSe pellet, and concentrated Se pellet; as previously described by Meyer et al (2010)) were blended to meet Se and ME levels as dictated by Se and nutritional intake treatments for each ewe. As for diets fed during early gestation, the Se source of the HSe pellet was the previously described Se-enriched wheat mill run, and the Se source of the ASe pellet was feedstuffs used in the diet.…”
Section: Gestationmentioning
confidence: 99%
“…Our sheep research model utilizing artificial rearing has demonstrated that many alterations caused by maternal nutrition extend past gestation and into neonatal (Meyer et al, 2010b) and market-weight lambs (Neville et al, 2010a). Maternal changes in body composition Carlson et al, 2009;Meyer et al, 2010b), endocrine and metabolic status (Ward et al, 2008;Lekatz et al, 2010), and colostrum yield and nutrient content (Swanson et al, 2008) have accompanied changes observed in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal changes in body composition Carlson et al, 2009;Meyer et al, 2010b), endocrine and metabolic status (Ward et al, 2008;Lekatz et al, 2010), and colostrum yield and nutrient content (Swanson et al, 2008) have accompanied changes observed in offspring. Therefore, we hypothesized that gestational nutrition alters the subsequent milk production of the dam, even when nutrient requirements of lactation are met.…”
Section: Introductionmentioning
confidence: 99%